Effects of operational parameters on dark fermentative hydrogen production from biodegradable complex waste biomass. (April 2016) - Ghimire, Anish; Sposito, Fabio; Frunzo, Luigi; Trably, Eric; Escudié, Renaud; Pirozzi, Francesco; Lens, Piet N.L.; Esposito, Giovanni
Highlights: Combination of initial pH and F/M ratio affects H2 yields from DF of food waste. Alkaline pre-treatment enhances the dark fermentative conversion of rice straw. Inoculum source and pre-treatment conditions influence H2 yields in DF of OMWW. The selection of optimal operating parameters depends on substrate biodegradability. Abstract: This work aimed to investigate the effect of the initial pH, combination of food to microorganism ratio (F/M) and initial pH, substrate pre-treatment and different inoculum sources on the dark fermentative biohydrogen (H2 ) yields. Three model complex waste biomasses (food waste, olive mill wastewater (OMWW) and rice straw) were used to assess the effect of the aforementioned parameters. The effect of the initial pH between 4.5 and 7.0 was investigated in batch tests carried out with food waste. The highest H2 yields were shown at initial pH 4.5 (60.6 ± 9.0 mL H2 /g VS) and pH 5.0 (50.7 ± 0.8 mL H2 /g VS). Furthermore, tests carried out with F/M ratios of 0.5, 1.0 and 1.5 at initial pH 5.0 and 6.5 revealed that a lower F/M ratio (0.5 and 1.0) favored the H2 production at an initial pH 5.0 compared to pH 6.5. Alkaline pre-treatment of raw rice straw using 4% and 8% NaOH at 55 °C for 24 h, increased the H2 yield by 26 and 57-fold, respectively. In the dark fermentation of OMWW, the H2 yield was doubled when heat-shock pre-treated activated sludge was used as inoculum in comparison to anaerobic sludge. Overall, this study shows that the application of different operating parameters to maximize the H2 yields strongly depends on the biodegradability of the substrate.